Detrital zircon geochronology of the Permian Lower Shihezi Formation, northern Ordos Basin, China: time constraints for closing of the Palaeo-Asian Ocean. (11th September 2022) - Chen, Rong; Wang, Feng; Li, Zhen; Evans, Noreen J; Chen, Hongde
Abstract: Temporal constraints on the closure of the eastern segment of the Palaeo-Asian Ocean along the northern margin of the North China Craton (NCC) remain unclear. As a part of the NCC, the sedimentation and tectonic evolution of the Late Palaeozoic Ordos Basin were closely related to the opening and closing of the Palaeo-Asian Ocean. We use petrology, quantitative mineralogical analysis, U–Pb geochronology and trace element signatures of detrital zircons of the Lower Shihezi Formation from two sections in the eastern north Ordos Basin and two sections in the western north Ordos Basin to reconstruct the sedimentary provenance and tectonic background of the northern Ordos Basin. The results show that the sediments of the western sections were mainly derived from the Yinshan orogenic belt and Alxa block, and that those in the eastern sections only came from the Yinshan orogenic belt. The trace element ratios in detrital zircons from the Late Palaeozoic sandstones indicate that the source areas were mainly subduction-related continental arcs, closely related to the continued subduction of the Palaeo-Asian Ocean in the Late Palaeozoic. Since the main Late Palaeozoic magmatic periods vary on the east and west sides of the northern margin of the Ordos Basin, two main collisions related to Palaeo-Asian Ocean closure are recorded. The collision on the west side occurred significantly earlier than that in the east. This study implies that the Palaeo-Asian Ocean began to subduct beneath the NCC in the Carboniferous and gradually closed from west to east thereafter.